KONTROVERSI MUSHAF USMANI: (Talaah Kritis Terhadap Riwayat Penolakan Ibnu Mas’ud) - Dedi Eko Riyadi Hs.2 (STQINIS, 2025)
Abstract The controversy surrounding the compilation of the Uthmanic Mushaf is a significant topic in the history of the codification of the Quran. One aspect that often draws attention is the report of Abdullah bin Mas’ud's rejection of the Uthmanic Mushaf standard. This research aims to conduct a critical examination of these reports using a historical-critical approach. The main focus of the study is to assess the validity of the sanad (chain of transmission) and matan (content) of the reports regarding Ibn Mas’ud's stance, as well as the historical context of the mushaf's compilation under the leadership of Caliph Uthman bin Affan. The findings indicate that several reports suggesting Ibn Mas’ud's rejection have weaknesses in both sanad and matan. Additionally, the differing opinions among the companions were more rooted in the context of ijtihad and the diversity of readings (qira’at) that had developed across various regions of the Islamic world. This research also reveals that Caliph Uthman's actions in unifying the mushaf aimed to preserve the unity of the Muslim community and prevent division due to differences in recitation. Therefore, the reports of Ibn Mas’ud's rejection should be understood within the framework of internal dialogue among the companions, without undermining the importance of maintaining the authenticity of the Quran. This study contributes to enriching the discourse on the history of the codification of the Quran and offers a new perspective on issues often viewed as controversial within Islamic scholarly tradition. Keywords: Uthmanic Mushaf, Ibn Mas’ud's Rejection Reports